2001
DOI: 10.1076/phbi.39.s1.63.0006
|View full text |Cite
|
Sign up to set email alerts
|

The Ethnomedicinal Uses of Magnoliaceae from the Southeastern United States as Leads in Drug Discovery

Abstract: In Asia and North America, members of the family Magnoliaceae have been and are presently used extensively in indigenous herbal medicine. Many taxa of the genus Magnolia produce lignans and sesquiterpene lactones, some with considerable in vitro bioactivities. This review focuses on selected natural products of the genus Magnolia from the southeastern United States with demonstrated biological and pharmacological properties. Ethnomedicinal data obtained from the Native Americans of the southeastern United Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Magnolia grandiflora L. (Magnoliaceae) is widely used as a traditional medicine for the treatment of diarrhea, abdominal diseases, rheumatic arthritis, heart disturbances, high blood pressure, epilepsy, infertility and fever [10]. The aqueous extracts of flowers and leaves have been reported to exhibit cardiovascular effects [11] and was also used as an anticonvulsant in rat [12].…”
Section: Introductionmentioning
confidence: 99%
“…Magnolia grandiflora L. (Magnoliaceae) is widely used as a traditional medicine for the treatment of diarrhea, abdominal diseases, rheumatic arthritis, heart disturbances, high blood pressure, epilepsy, infertility and fever [10]. The aqueous extracts of flowers and leaves have been reported to exhibit cardiovascular effects [11] and was also used as an anticonvulsant in rat [12].…”
Section: Introductionmentioning
confidence: 99%
“…In China, flower buds of several species of Magnolia, which are very rich in essential oils, are an important part of Traditional Chinese Medicine [1]. In the Eastern and Southeastern United States Magnolia is represented by eight taxa, of which several have had medicinal importance in Native American medicinal systems and many species show various biological activities [2,3]. Magnolia is known for producing secondary metabolites such as essential oils, sesquiterpenes, lignans and neolignans, coumarins and alkaloids.…”
mentioning
confidence: 99%
“…It is an evergreen tree introduced during the conquest by the Spaniards and is now widely distributed in America. Ethnomedically, Magnolia grandiflora extracts have been used since ancient times to ameliorate cardiac pathologies, a practice that remains to this day (Schühly et al, 2001). Our previous study (del Valle-Mondragó n et al, 2004) showed that vulgarenol [3,4,9-trihydroxy-9-methyl3a,5,5a,9,9a,9b-hexahydronaphtho[1,2-b]furan-2,6 (3H,4H)-dione] (Fig.…”
Section: Introductionmentioning
confidence: 99%